Overexpression of AtWRKY28 and AtWRKY75 in Arabidopsis enhances resistance to oxalic acid and Sclerotinia sclerotiorum - Chen, Xiaoting; Liu, Jun; Lin, Guifang; Wang, Airong; Wang, Zonghua; Lu, Guodong (Plant cell reports, 2013)
KEY MESSAGE : Based on Arabidopsis microarray, we found 8 WRKY genes were up-regulated with Oxalic acid (OA) challenge, AtWRKY28 and AtWRKY75 overexpression lines showed enhanced resistance to OA and Sclerotinia sclerotiorum. The WRKY transcription factors are involved in various plant physiological processes and most remarkably in coping with diverse biotic and abiotic stresses. Oxalic acid (OA) is an important pathogenicity-determinant of necrotrophic phytopathogenic fungi, such as Sclerotina sclerotiorum (S. sclerotiorum) and Botrytis cinerea (B. cinerea). The identification of differentially expressed genes under OA stress should facilitate our understanding of the pathogenesis mechanism of OA-producing fungi in host plants, and the mechanism of how plants respond to OA and pathogen infection. Based on Arabidopsis oligo microarray, we found 8 WRKY genes that were up-regulated upon OA challenge. The Arabidopsis plants overexpressing AtWRKY28 and AtWRK75 showed enhanced resistance to OA and S. sclerotiorum simultaneously. Furthermore, our results showed that overexpression of AtWRKY28 and AtWRK75 induced oxidative burst in host plants, which suppressed the hyphal growth of S. sclerotiorum, and consequently inhibited fungal infection. Gene expression profiling indicates that both AtWRKY28 and AtWRKY75 are transcriptional regulators of salicylic acid (SA)- and jasmonic acid/ethylene (JA/ET)-dependent defense signaling pathways, AtWRKY28 and AtWRKY75 mainly active JA/ET pathway to defend Arabidopsis against S. sclerotiorum and oxalic acid stress.